PENEGAKAN HUKUM PIDANA PADA TINGKAT PENYIDIKAN TERHADAP PELANGGARAN PEREDARAN DAN PENJUALAN MINUMAN BERALKOHOL DI KOTA PONTIANAK - NIM. A1011171152, AGUSTINUS WAHYU HERY WIJAYANTO (Jurnal Fatwa Hukum, 2022)
ABSTRACTThis study discusses "Criminal Law Enforcement at the Investigation Level Against Violations of Circulation and Sales of Alcoholic Beverages in Pontianak City". This study is motivated by why criminal law enforcement at the level of investigation of violations and sales of alcoholic beverages in the city of Pontianak has not been maximized, there are dealers and sellers of alcoholic beverages who sell illegal alcoholic beverages, according to the regional regulation of the city of Pontianak Number 23 of 2002 concerning Supervision, Control, and Prohibition of the Circulation of Alcoholic Drinks that alcoholic beverages that are allowed to circulate in the community are alcoholic beverages of class A, and for sellers of alcoholic beverages the sellers must have a trading business license and a license for an alcoholic beverage business, but in the circulation of alcoholic beverages there are still many sellers who does not have a permit and sells alcoholic beverages in contravention of the regulation. The sale and circulation of alcoholic beverages that are in conflict with the regulation is a violation, where for sellers and dealers who violate the regulation can be subject to criminal sanctions. The circulation of illegal alcoholic beverages that are still widely available in the community indicates that law enforcement carried out by law enforcement officers is not optimal, not maximal law enforcement carried out by law enforcement officers can be caused by several factors so that an effort is needed from law enforcement officers. Based on research conducted, law enforcement has not been maximized at the level of investigation of violators of the circulation and sale of alcoholic beverages due to lack of coordination between law enforcement institutions and lack of public awareness. Keywords : abstract, jurnal, law, Law Enforcement, Violation of Circulation and Sales of Alcoholic Beverages ABSTRAKPenelitian ini membahas mengenai "Penegakan Hukum Pidana Pada Tingkat Penyidikan Terhadap Pelanggaran Peredaran dan Penjualan Minuman Beralkohol di Kota Pontianak". Penulisan dilatarbelakangi oleh mengapa penegakan hukum pidana pada tingkat penyidikan terhadap pelanggaran dan penjualan minuman beralkohol di Kota Pontianak belum maksimal, terdapat pengedar dan penjual minuman beralkohol yang menjual minuman beralkohol yang illegal, menurut peraturan daerah kota Pontianak Nomor 23 Tahun 2002 Tentang Pengawasan, Pengendalian, dan Pelarangan Peredaran Minuman Beralkohol bahwa minuman beralkohol yang di izinkan untuk beredar di masyarakat adalah minuman beralkohol golongan A, serta bagi penjual minuman beralkohol para penjual harus memiliki surat izin usaha perdagangan dan surat izin tempat usaha minuman beralkohol, namun dalam peredaran minuman beralkohol masih banyak penjual yang tidak memiliki izin serta menjual minuman beralkohol yang bertentangan dengan perda tersebut. Penjualan dan peredaran minuman beralkohol yang bertentangan dengan perda tersebut merupakan suatu pelanggaran, dimana bagi penjual dan pengedar yang melanggar perda tersebut dapat dikenakan sanksi pidana. Peredaran minuman beralkohol yang illegal yang masih banyak di lingkungan masyarakat menandakan bahwa penegakan hukum yang dilakukan oleh aparat penegak hukum belum maksimal, belum maksimalnya penegakan hukum yang dilakukan oleh aparat penegak hukum dapat disebabkan oleh beberapa faktor sehingga diperlukan suatu upaya dari aparat penegak hukum. Berdasarkan penelitian yang dilakukan bahwa belum maksimalnya penegakan hukum pada tingkat penyidikan terhadap pelanggar peredaran dan penjualan minuman beralkohol dikarenakan kurangnya koordinasi antara institusi penegak hukum serta kurangnya kesadaran masyarakat. Kata Kunci : abstrak, jurnal, hukum, Penegakan Hukum, Pelanggaran Peredaran dan Penjualan Minuman Beralkohol.